Understanding Muslim Mobilities and Gender - Thimm, Viola (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Complex dynamics emerge around im/mobility that are related to social relations, identifications and power in many parts of the contemporary world. The manifold ways in which Muslims engage the possibilities of mobile lives show the tremendous creative potential of these practices. Coming from different disciplines and regional contexts, the contributors to this book investigate the myriad connections between Islamic concepts, Muslim practices, and gender and mobility theories. Their findings contribute to the mobility debate by revealing that im/mobile lives of people are deeply rooted in religious and/or gendered backgrounds and social structures and furthermore invite a critical rethinking of the concept of mobility itself